Оцінка екосистемних послуг лісових ландшафтів Харківської області та прогноз їх використання - Воронін , Владіслав Олександрович; Voronin , V.O. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Робота присвячена оцінці екосистемних послуг лісових ландшафтів Харківської області, на основі геоекологічної оцінки ландшафту засобами ландшафтно-екологічного планування, аналізу методів та підходів до оцінки екосистемних послуг, виявленню методологічних проблем у поєднанні екологічної та економічної оцінки лісових ландшафтів Харківської області, прогнозуванню використання концепції екосистемних послуг для сталого управління лісовими ландшафтами.

The work is devoted to the assessment of ecosystem services of forest landscapes of the Kharkiv region, based on the geoecological assessment of the landscape by means of landscape and ecological planning, the analysis of methods and approaches to the assessment of ecosystem services, the identification of methodological problems in the combination of ecological and economic assessment of forest landscapes of the Kharkiv region, forecasting the use of the concept of ecosystem services for sustainable management of forest landscapes.
Assessment of ecosystem services of forest landscapes of Kharkiv region and forecast of their use
Keywords: FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; лісові ландшафти; ландшафтно-екологічне планування; лісові екосистеми; природні екосистеми; соснові насадження; фітоценози; ґрунти; ГІС; візуалізація; екосистемні послуги; лісові пожежі; сталий розвиток громад; forest landscapes; landscape-ecological planning; forest ecosystems; natural ecosystems; pine plantations; phytocenoses; soils; GIS; visualization; ecosystem services; forest fires; sustainable development of communities